Saccadic body turns in walking Drosophila - Geurten, Bart R. H.; Jähde, Philipp; Corthals, Kristina; Göpfert, Martin C. (Frontiers in Behavioral Neuroscience, 2014)
Drosophila melanogaster structures its optic flow during flight by interspersing translational movements with abrupt body rotations. Whether these ‘body saccades’ are accompanied by steering movements of the head is a matter of debate. By tracking single flies moving freely in an arena, we now discovered that walking Drosophila also perform saccades. Movement analysis revealed that the flies separate rotational from translational movements by quickly turning their bodies by 15 degrees within a tenth of a second. Although walking flies moved their heads by up to 20 degrees about their bodies, their heads moved with the bodies during saccadic turns. This saccadic strategy contrasts with the head saccades reported for e.g. blowflies and honeybees, presumably reflecting optical constraints: modelling revealed that head saccades as described for these latter insects would hardly affect the retinal input in Drosophila because of the lower acuity of its compound eye. The absence of head saccades in Drosophila was associated with the absence of haltere oscillations, which seem to guide head movements in other flies. In addition to adding new twists to Drosophila walking behavior, our analysis shows that Drosophila does not turn its head relative to its body when turning during walking.